تأثير تبني المسؤولية البيئية في تحسين صورة المؤسسة لدى الزبون -دراسة إحصائية لعينة من زبائن مؤسسة "جازي" - لاغة, سمية; بولفراخ, سارة (جامعة الوادي - University of Eloued, 2019)
The aim of this research paper is to identify the impact of Djezzy’s adoption of environmental responsibility on its image to its customers. To achieve these objectives, the questionnaire was designed for the purpose of obtaining preliminary data consisting of 9 paragraphs, distributed to a sample of 242 customers to the Djezzy enterprise in Setif province, where data was collected and analyzed and then tested the main hypothesis through the SPSS20 program, using several statistical methods and measurements. In the end of this study we have found a number of results including: - Environmental awareness of the Respondents, and the high level of acceptance. - The most of the study sample were agreed in all the statements that reflect Djezzy’s image.
مقال
Keywords: مسؤولية بيئية ; صورة المؤسسة ; زبائن مؤسسة جازي